NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM PELAKSANAAN TRADISI ZIARAH KUBUR PUYANG RIE DINDING - Aryana, Dalika; Idi, Abdullah; Ali, Mukti; Pratama, Irja Putra; Syarnubi, Syarnubi; Fadil, Achmad (PAI RAFAH, 2024)
The pilgrimages that the residents of Simpang Tanjung village make to the village's grave of Puyang Rie Dinding serve as the inspiration for this study's ancestral practices. This mausoleum is frequented by numerous townspeople as well as tourists from outside the hamlet, both singly and in groups. This research tries to explain how the values of Islamic religious education are applied in the pilgrimage tradition of Puyang Rie Dinding's tomb. This research uses qualitative field research. Direct observation of the condition of eating Puyang Rie Dinding, interviews with caretakers, community leaders, and various communities, as well as documentation in the form of objects in the tomb of Puyang Rie Dinding and relics of Puyang Rie Dinding, were used as data collection techniques. Descriptive analysis is the data analysis method used. First, the community believes that the tomb of Puyang Rie Dinding is a mustajab location when someone has nazdar there, although Some people do not accept it. Secondly, the results of temporary research reveal that when a person has fulfilled his or her wish, then he or she must fulfill the vow or nazdar that was made during the pilgrimage. When one travels to the tomb, the promise goes along with the act of paying nazdar. Secondly, the locals think that their practice is permissible in Islam, the religion they follow. Third, Puyang Rie Dinding's grave pilgrimage tradition has distinctive characteristics. The importance of Islamic Religious Education to Allah, His Messenger, and oneself is one of Islamic Religious Education, which is also reflected in the custom of grave pilgrimage to the grave of Puyang Rie Dinding.